Kajian input-output wilayah: aplikasi dan analisis di Selangor - Saari, Mohd Yusof; Abdul Rashid, Zakariah (Penerbit Universiti Kebangsaan Malaysia, 2008)
The paper presents the result of the development of regional input-output table which estimated by using the RAS technique. With assuming the production structure and technology are identical, the regional input-output is estimated based on the national input-output table. By developing the input-output table, the study has improved state's GDP accounting for both by expenditures and products in consistent way. Even though the studies found that the manufacturing, mining and quarrying, and government services have modest production structure, inter-industry linkages effects indicate that these sectors are the key sectors for Selangor.